Why are chiefs recognised in South Africa's new democracy? Issues of legitimacy and contestation in local politics: a case study of chiefly and local government in Vaaltyn - Skosana, Dineo Ephodia (My University, 2013)
This thesis examines the legitimacy of chiefs in post-apartheid South Africa through the prism of the Vaaltyn Mokopane chieftainship in Limpopo Province. It is used as a case study to understand how chiefs gain and maintain legitimacy. This is studied within a framework of a succession dispute between two candidates, Vaaltyn A (born in 1964) and Vaaltyn B (born in 1974). The claim of Vaaltyn B was legitimized by the local government of Mokopane and the provincial government of Limpopo, irrespective of the fact that that majority of the Kekana tribal council and the community members supported Vaaltyn A. The thesis suggests that the legitimacy of chief Vaaltyn B is maintained through patron-client relations in which the local/provincial government enters into and initiates economically viable relations with Vaaltyn B and mining houses. These patron-client relations are formed and continued within a context of a succession dispute which allows for Vaaltyn A and community members to be sidelined. Finally, the thesis discusses where the legitimization of chief Vaaltyn B by the people stands, in this case where authority has already been awarded by the government. This serves as a platform to probe whether people continue to support the continuing existence of chiefs in a democratic dispensation.
M.A.--University of the Witwatersrand, Faculty of Humanities, 2012